UJI VALIDITAS MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY (AR) DALAM MENGENAL HEWAN BUAS PADA ANAK USIA DINI - Permata, Rista Dwi; Ekayati, Ifa Aristia Sandra; Allan Firman , Allan Firman (Pusat Penelitian dan Pengabdian kepada Masyarakat STKIP Citra Bakti, 2025)
This study aims to develop Augmented Reality (AR) based media in recognizing wild animals in early childhood. This study is a Research and Development (R n D) study with a development model described by Sugiyono (potential and problems, data collection, product design, design validation, design revision, product trial, product revision, usage trial, product revision, and mass production). The data used in this study is validation from experts who are lecturers in charge of courses at the PG PAUD UNIROW Study Program. Data collection used is observation and interviews. The results of this study are the validity of Augmented Reality-based media of 91.1% with quality research that Augmented Reality (AR) based media can be used in learning for early childhood.